Induction of Myelinating Oligodendrocytes in Human Cortical Spheroids - Madhavan, Mayur (Nat Methods, 2018)
Organoid technologies provide an accessible system to examine cellular composition, interactions, and organization in the developing human brain, but previously have lacked oligodendrocytes, the myelinating glia of the central nervous system. Here we reproducibly generate oligodendrocytes and myelin in human pluripotent stem cell-derived “oligocortical spheroids”. Transcriptional, immunohistochemical, and electron microscopy analyses demonstrate molecular features consistent with maturing oligodendrocytes by 20 weeks in culture, including expression of MYRF, PLP1, and MBP proteins and initial myelin wrapping of axons, with maturation to longitudinal wrapping and compact myelin by 30 weeks. Promyelinating drugs enhance the rate and extent of oligodendrocyte generation and myelination, while oligocortical spheroids generated from patients with a genetic myelin disorder recapitulate human disease phenotypes. Oligocortical spheroids provide a versatile platform to observe and dissect the complex interactions required for myelination of the developing central nervous system and offer new opportunities for disease modeling and therapeutic development in human tissue.